Can providing daily iron-fortified lunches to school-going children living in an impoverished Guatemalan community improve iron status? - Llesenia Massey; Steven McGeehan; Manichanh Ratts; Thomas Mitchell; Christopher Cotten; Alejandra Perez; Kathy Beerman (Inishmore Laser Scientific Publishing Ltd, 2023)
# Background Iron deficiency anemia (IDA) remains one of the most common diet-related micronutrient deficiency disorders in the world. Although iron supplementation can effectively improve iron status, it is often a short-term solution to this endemic, chronic health problem. Lucky Iron Fish® (LIF) offers a novel, long-term approach to treat IDA that can be easily utilized in regions of the world where IDA is most prevalent. While the beneficial use of LIF for household preparation of meals has been demonstrated, its use in quantity food production has not been investigated. The purpose of this study was to develop methodology for large-scale iron fortification of cooking water and to assess changes in hemoglobin and hematocrit values in school-going children following 8 months of receiving iron-fortified school lunches prepared with LIF. # Methods Laboratory studies were conducted to develop the protocol to prepare iron fortification of cooking water using LIF. Study participants were school-going children from economically, disadvantaged families attending private schools in Jocotenango, Guatemala. Baseline measures (weight, height, hemoglobin, and hematocrit) were taken at the start and completion of the academic calendar. The sample was divided into quintiles based on pre-hemoglobin and hematocrit values where quintile 1 had the lowest baseline hemoglobin and hematocrit values and quintile 5 had the highest baseline hemoglobin and hematocrit values. Paired t-tests were used to determine if there were overall significant pre- and post-differences in iron status values by quintile groupings. # Results A total of 286 (77%) of children between the ages of 5 -- 16 (y) completed the study. Post- hemoglobin values were significantly higher than pre-hemoglobin values for those in quintile 1, whereas post-hematocrit values significantly increased for quintiles 1 and 2. # Conclusions Study results suggest that LIF can be used to prepare large quantities of food and that regular consumption of iron-fortified school lunches can improve iron status in children with marginal status. Equally important is the finding that iron-fortified meals do not negatively impact those with healthy iron values.